Effective dose of radiation on the eye, thyroid and pelvic region resulting from exposures to the Galileos comfort cone beam computerized tomographic scanner - Phanzu, Bwanga (My University, 2015)
Introduction: Dental Cone beam CT has encountered great success in diagnostics and treatment planning in dentistry. However, it makes use of ionizing radiation. Lots of concern on the effects of x-rays on vital organs of the head and neck region has been raised. Clarity on the amount of radiation received on these specific organs will be a contribution to a better use of the emergent technology. Aim: The aim of this study is to determine the potential dose of radiation received on the eye and thyroid and to quantify the amount of potential scatter on the gonads during CBCT examinations. Material and Methods: Calibrated Lithium- Fluoride thermoluminescent dosimeters were inserted inside an anthropomorphic phantom, on sites of the eye, thyroid and the gonads. After its submission to a CBCT examination, using the high and standard resolution for a similar scanning protocol, the dose of radiation received on each organ was calculated according to the ICRP guidelines. Results: An equivalent dose of 0.059 mGy was calculated for the eye. Compared to the threshold dose of 0.5 Gy fixed by the ICRP 2007, this can be considered as relatively low. The thyroid with an effective dose of 23.5 μSv represented 20% of the full body effective dose existing in literature. The gonads absorbed an effective dose of 0.05 μSv, which was considered as negligible. Conclusion: The doses calculated were considered as relatively low. However, dentists must be aware of risks of cumulative exposure. Therefore adherence to the ALARA principle and consideration of clinical indication for CBCT remain a priority.
Degree of Master of Science in Dentistry by coursework and dissertation A research report submitted to the Faculty of Health Sciences, University of the Health Sciences. University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Dentistry Johannesburg, 2014
Keywords: Dose-Response Relationship, Radiation; Radiation Dosage